THE ROLE OF MAQASHIDUS SHARI'AH THEORY IN THE FORMATION OF ISLAMIC INSURANCE LEGAL FATWA - Sugeng Riyadi (International Journal of Multidisciplinary Reseach, 2025)
This study examines the pivotal role of Maqashidus Shari'ah theory in shaping legal fatwas (Islamic legal opinions) for Islamic insurance (takaful) products and practices. Through a comprehensive analysis of contemporary fatwa-making processes, this research investigates how the five fundamental objectives of Islamic law preservation of life (hifz al-nafs), intellect (hifz al-aql), lineage (hifz al-nasl), wealth (hifz al-mal), and religion (hifz al-din) serve as guiding principles in determining the Shari'ah compliance of insurance mechanisms. The study employs a qualitative methodology, analyzing fatwa documents from major Islamic jurisprudence councils and examining theoretical frameworks established by contemporary Islamic scholars. Findings reveal that Maqashidus Shari'ah theory provides a robust foundation for addressing modern financial challenges while maintaining Islamic ethical principles. The research demonstrates that fatwas on Islamic insurance consistently reference maqashid principles to justify risk-sharing mechanisms, mutual cooperation (ta'awun), and the elimination of prohibited elements such as gharar (excessive uncertainty), riba (usury), and maysir (gambling). This study contributes to the growing body of literature on Islamic finance jurisprudence and offers practical insights for Islamic financial institutions, regulatory bodies, and scholars engaged in contemporary ijtihad (independent reasoning).